MEDIA PEMBELAJARAN BERBASIS IPTEK SEBAGAI SARANA PENDIDIKAN AGAMA ISLAM DI ERA SOCIETY 5.0 - Agustin, Maulid (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
Society 5.0 is a concept to create a society that focuses on human development based on cutting-edge technology. The era of Society 5.0 is focused on providing products and services specifically designed for various individual needs and the needs of many people to create benefits in the social sector. Islamic religious education can be the most up-to-date solution in its mission to make benefits in the social sector for all humans. So, we need an Islamic learning media launched on a science and technology basis to strengthen the implementation of the Society 5.0 concept. The research method used is a literature study by collecting data from various relevant sources. The research results show that using technology in Islamic religious learning can increase learning effectiveness and student engagement. Several science and technology-based learning media such as mobile applications, digital platforms, augmented reality (AR) and virtual reality (VR), webinars and online conferences, social media, and e-learning can simplify the learning process and increase students' understanding. However, challenges such as accuracy and authenticity of content, as well as monitoring inappropriate content, need to be addressed, as well as the potential and limitations of technology-based learning media in Islamic education. Apart from that, Islamic Religious Education teachers need to control the use of technology so that it continues to lead to a human-centered approach